Kesantunan Dan Daya Pragmatik Tindak Tutur Direktif Paslon Pemilihan Gubernur Di Wacana Politik Skh Nasional Dan Implikasinya Sebagai Bahan Ajar Bahasa Indonesia Di SMP - Saputra, Hermawan Adi; , Prof. Dr. Harun Joko Prayitno, M.Hum (2017)
The aim of this research is including three things, (1) to describe the form of direct mannerliness act of paired governors' candidates in political discourse of national daily newspaper, (2) to describe the pragmatic effort of paired governors' in political discourse of national daily newspaper, (3) to describe the implication of direct mannerlines act in political discourse of national daily newspaper towards Indonesian language lesson planning in Junior High School. This research had been done on the speech of paired governors' candidates of DKI Jakarta on the daily National (Kompas). This research is using qualitative descriptive method, and using embedded research strategy. Technique in collecting the data is using gathering and note-taking technique. The results of the research consist of three results about direct mannerliness act and pragmatic effort that consist of 30 data. 1) The form of direct mannerliness act of paired governors' candidates, as follows: targeting, ordering, directing, offering, proposing, hoping, begging, suggesting, recommending, prosecuting, proclaiming, requesting, supporting, giving advice, encouraging, challenging, instructing, reminding, preventing, prohibiting, asking, criticizing, and urging. 2) Pragmatic effort of paired governors' candidates on politic expression containing six efforts: jeering, criticizing, teasing, threatening, prosecuting, insisting, and ordering. 3) The impleentation of direct mannerlines act towards Indonesian Language lesson planning on first semester of grade VIII within point 1.2 of Basic Competence about perceiving reports' contents.